2021
DOI: 10.1021/acsami.1c14918
|View full text |Cite
|
Sign up to set email alerts
|

Methane Dry Reforming by Ni–Cu Nanoalloys Anchored on Periclase-Phase MgAlOx Nanosheets for Enhanced Syngas Production

Abstract: Stable and efficient syngas production via methane dry reforming is highly desirable as it utilizes two greenhouse gases simultaneously. In this work, active Ni–Cu nanoalloys stably anchored on periclase-phase MgAlO x nanosheets were successfully synthesized by a hydrothermal method. These highly dispersed small Ni–Cu alloys strongly interacted with the periclase-phase MgAlO x nanosheets, on which abundant base sites were accessible. On the optimal catalyst (6Ni6CuMgAl–S), methane and carbon dioxide conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…(2) The alloying of Cu with Ni would influence CH 4 activation on the Ni surface, and the activation energy of CH 4 on the alloy surface was smaller than that on pure Ni surface, which led to the higher CH 4 conversion . (3) Cu modification alleviated the deep cracking of CH x on Ni by the reaction O + CH x → CO + H 2 at the Ni–Cu interface, which contributed to less carbon deposition …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The alloying of Cu with Ni would influence CH 4 activation on the Ni surface, and the activation energy of CH 4 on the alloy surface was smaller than that on pure Ni surface, which led to the higher CH 4 conversion . (3) Cu modification alleviated the deep cracking of CH x on Ni by the reaction O + CH x → CO + H 2 at the Ni–Cu interface, which contributed to less carbon deposition …”
Section: Resultsmentioning
confidence: 99%
“…54 (3) Cu modification alleviated the deep cracking of CH x on Ni by the reaction O + CH x → CO + H 2 at the Ni−Cu interface, which contributed to less carbon deposition. 55 3.4. Characterization of Used Catalysts.…”
Section: Catalytic Performance Of Mdrmentioning
confidence: 99%
“…They determined the optimum conditions: 10 wt % of Ni, 0.83 wt % of Cu, and 750 °C. Xiao et al 235 investigated the DRM activity of different Ni/Cu ratio alloys anchored on the peritectic phase MgAlO x nanosheets. The results of H 2 -TPR (Figure 7a) showed that a higher reduction temperature was required with the addition of Cu, which implied that the interaction of the metal something carriers was enhanced.…”
mentioning
confidence: 99%
“…In the field of heterogeneous catalysis by metals, bimetallic catalysts are promising for performing challenging chemical transformations, [26][27][28][29][30][31] and the ensemble effect is a well-known phenomenon. 32 The main feature of this effect is that reactions are sensitive to alloying with a second metal within the group of adjacent atoms of the active metal that are required for forming chemisorption complexes.…”
mentioning
confidence: 99%
“…Electronic effects in alloy catalysts refer to the formation of a bond between two different metals that can induce substantial electronic perturbations leading to changes in the chemical and catalytic properties of the bonded metals. [26][27][28][29][30][31] In this context, it is important to establish if bimetallic nickel catalysts, such as NiCu/CeO2, can be useful for tuning the degree of dehydrogenation of CHx (x= 13) species on Ni/CeO2 surfaces, which is critical for preventing coke formation and crucial in the direct partial oxidation of methane to methanol or in the conversion of CHx groups into high value chemicals like olefins or aromatics.…”
mentioning
confidence: 99%